Peningkatan Pengetahuan Kepada Ibu Hamil tentang Kehamilan Risiko Tinggi di Rumah Pelita Manyaran - Azizah, Agtika Yasyfa Nur (Kreativasi : Journal of Community Empowerment, 2024)
Maternal mortality rates (MMR) are frequently used to evaluate a community's level of health. In general, the effectiveness of maternal health initiatives may also be assessed using MMR. One factor that contributes to the maternal mortality rate is high-risk pregnancies. High-risk pregnancies are those that have conditions that might raise the fetus's chance of abnormalities or injury. Low- and lower-middle-income nations, such as Indonesia, account for about 95% of all maternal mortality. Numerous studies have have shown that pregnant women lack knowledge of health risks during pregnancy. A potential strategy for lowering MMR is educating women about high-risk pregnancies. The purpose of this community service project is to educate expectant mothers about pregnancy risks in order to reduce complications for both the mother and the fetus at Rumah Pelita Manyaran, Semarang City. Providing education is done through the counseling method. The media used is leaflet media. Pregnant women who attended the Pregnant Women Class at Rumah Pelita Manyaran in Semarang City were the targets of this social project. The results of the measurement indicated a significant growth in knowledge. Pregnant women in the good category had a knowledge level of 45% before counseling, and that level of knowledge increased to 60% after counseling.